Exome sequencing detected an extremely rare case of foetal onset familial haemophagocytic lymphohistiocytosis type 5 presenting with hydrops foetalis - V. Thadchanamoorthy; M. T. R. Jayatunga; Kavinda Dayasiri; E. Jasinge; M. L. M. Jinnah; C. Pereira; V. Skrahina; Markandu Thirukumar (BMC, 2021)
Abstract Background Familial hemophagocytic lymphohistiocytosis (FHL) is a genetically heterogeneous autosomal recessive hyper-inflammatory syndrome which needs early accurate diagnosis and appropriate treatment to prevent complications and early mortality. Recently, it was reported that mutations in STXBP2 gene are linked to FHL type 5 (FHL-5). Case Presentation We report a Sri Lankan neonate who presented with low Apgar scores at birth, abdominal distension, and hepatosplenomegaly, followed by lethargy, poor sucking and rapid decompensation with wide spread activation of inflammation within 48 h of birth. Her elder sibling also had a similar presentation during early neonatal period and deceased at two weeks of age with no diagnosis. Unfortunately, the index case deceased at 14 days of age following multi-organ dysfunction and severe metabolic acidosis. Targeted gene panel followed by reflex exome sequencing revealed a novel likely pathogenic homozygous variant in the STXBP2 gene (NM_001272034.1:c.1141-2A > G) which confirmed the diagnosis of autosomal recessive FHL-5. Conclusion Early diagnosis of FHL type 5 using genetic analysis and timely treatment are difficult in the absence of family history due to a wide spectrum of clinical manifestations. However both early diagnosis and treatment doesn't alter the long term prognosis. So genetic counselling would be the better option.